Physical, Physicochemical, Mechanical, and Structural Characterization of Films Based on Gelatin/Glycerol and Carbon Nanotubes - Israel Sifuentes-Nieves; Rodolfo Rendón-Villalobos; Antonio Jiménez-Aparicio; Brenda Hildeliza Camacho-Díaz; Gustavo Fidel Gutiérrez López; Javier Solorza-Feria (International Journal of Polymer Science)
A new method to prepare glycerol/gelatin based films, by doping the film with carbon nanotubes (CNTs) and sodium dodecyl sulfate (SDS), was proposed. SDS was used to disperse CNTs in gelatin/glycerol films as follows: gelatin/glycerol (GG) incubated with equal concentrations of CNT and SDS; GG with 0.001% w/w CNT/SDS; GG with 0.002% CNT/SDS and GG with 0.004% CNT/SDS. Diffractograms of CNT/SDS /glycerol films showed an amorphous structure, being consistent with thermograms involving temperature and fusion enthalpy. Mechanical tests showed 30% increase in elongation at break of GG with 0.004% CNT/SDS, with respect to gelatin/glycerol/SDS control. Samples with CNT had increased water vapor permeability (WVP). The film fractal dimension indicated that, with the addition of the highest concentration of CNT, films with a homogeneous surface were obtained, with probable nanotube inclusion in the protein matrix. According to the results, the easy method used to prepare gelatin composite materials gave place to films with better physical, mechanical, and thermal properties.